Sustainability Of Ngaben Culture In Balinese Transmigration - Abdul Malik Iskandar; Arfenti Amir; Syamsul Alam; Harifuddin; Andi Herlina (International Journal of Educational Research & Social Sciences, 2022)
Cultural diversity is a necessity. Every tribe has own culture. The aim of study is to analyze the description of Ngaben ceremony procession, the sustainability or survival of Ngaben culture and the perception of local community in Balinese transmigration communities in Martajaya Village, Pasangkayu Regency. This study applied descriptive qualitative method by taking informants intentionally based on certain considerations obtained through in-depth interviews, observation, and documentation. Data were obtained and tested for the validity of the data by means of triangulation, extending observations, Focus Group Discussion (FGD).The results of study showed that 1) Ngaben ceremony was directly held for some days with various long time and sacred processes with the aim of being able to return to the creator without any obstacles and being reincarnated for the better in every ritual, 2) there are two types of Ngaben namely Sawa Wedana Ngaben is carried out by people who are able to do it individually, while mass Ngaben is carried out in mutual cooperationonce every five years, 3) the local community perception of Ngaben that they are used to and can tolerate the culture and customs of the Balinese community. Ngaben is a good culture and full of meaning in life.